Egner vintertoktet seg til overvåking av endringer i fiskesamfunnet i Barentshavet? : en gjennomgang av metodikk og data fra 1981-2007 - Johannesen, Edda; Wenneck, Thomas de Lange; Høines, Åge S.; Aglen, Asgeir; Mehl, Sigbjørn; Mjanger, Hildegunn; Fotland, Åge; Halland, Tor Ivar; Jakobsen, Tore (Havforskningsinstituttet, 2009)
The winter survey (1981-) is the longest bottom trawl time series in the Barents Sea. The survey is used as tuning series in cod and haddock assessment, but change and ecosystem-based management, necessitates the study of changes in abundance and distribution of other species as well. However, the way the survey has been conducted has changed over time. In this report we sum up the most important changes in the way the winter survey has been conducted, and evaluate the potential for using the survey to study changes in the Barents Sea fish community.